circRNA Expression Profile in Dental Pulp Stem Cells during Odontogenic Differentiation - Ming Chen; Yeqing Yang; Junkai Zeng; Zilong Deng; Buling Wu (Hindawi Limited, 2020)
Introduction. Odontogenic differentiation of human dental pulp stem cells (hDPSCs) is a key step of pulp regeneration. Recent studies showed that circular RNAs (circRNAs) have many biological functions and that competing endogenous RNA (ceRNA) is their most common mechanism of action. However, the role of circRNAs in hDPSCs during odontogenesis is still unclear. Methods. Isolated hDPSCs were cultured in essential and odontogenic medium. Total RNA was extracted after 14 days of culture, and then, microarray analysis was performed to measure the differential expressions of circRNAs. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was then performed to validate the microarray results. Based on microarray data from this study and available in the database, a ceRNA network was constructed to investigate the potential function of circRNAs during odontogenesis. In addition, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed to investigate the potential correlation between signaling pathways and circRNAs. In addition, qRT-PCR and Western blot analysis were used to explore the function of hsa_circRNA_104101. Results. We found 43 upregulated circRNAs and 144 downregulated circRNAs during the odontogenic differentiation process (fold change>1.5 and <-1.5, respectively; P<0.05). qRT-PCR results were in agreement with the microarray results. Bioinformatic analysis revealed that the Wnt signaling pathway and the TGF-β signaling pathway, as well as the other pathways associated with odontogenic differentiation, were correlated to the differentially expressed circRNAs. hsa_circRNA_104101 was proved to promote the odontogenic differentiation of hDPSCs. Conclusion. This study reported 187 circRNAs that were differentially expressed in hDPSCs during odontogenic differentiation. Bioinformatic analysis of the expression data suggested that circRNA-miRNA-mRNA networks might act as a crucial mechanism for hDPSC odontogenic differentiation, providing a theoretical foundation for the study of pulp regeneration regulation by circRNAs.